Crenças e percepções das mulheres saudáveis sobre câncer de mama: uma revisão sistemática da literatura - Porto, Gláucia Pina Guimarães (2018)
Understanding breast health from needs and conditions in a socially contextualized way can be a way to develop consistent public policies for the promotion of breast and woman health as a tool for the prevention and early detection of breast cancer through institutions and organizations committed to social development in combating the disease. The overall objective of this study was to conduct a systematic review of the literature regarding the beliefs and perceptions that healthy women have about breast cancer. The research problem arose from the observation of the psychosocioeducational difficulties of women in cases of breast cancer, as well as for preventive care and early detection of the disease, for approximately two years, in a pilot project of health intervention with emphasis on the public roles of women in the fight against breast cancer, through an intervention research with a multidisciplinary character. The method was the systematic review of literature. The initial selection of articles was done through the reading of the title and abstract, and the exclusion of duplicate results was performed by the identification of the main author. As an inclusion criterion for the analysis of the results, the strength of evidence of the selected studies was summarized and the relevance of the most interesting descriptors was considered, aiming at the accomplishment of a qualitative synthesis. From 2,926 studies found, 96.24% were mastectomized women, and 2.90% were eligible studies whose study object considers behaviors of healthy women, their beliefs, perceptions and / or knowledge about prevention and early detection of the disease . The results indicate that the production of knowledge about the problem is scarce, with consequences on the limits of changing beliefs and perceptions about breast cancer. The reassignment of healthy women on breast cancer based on correct information can increase the rate of detection of the disease, which can avoid many deaths, and reduce the expenditure of public funds with treatments for advanced diagnoses. This change in attitude makes it possible for early detection not to be seen as a threat but as the best path to health